Dynamics of Corporate Performance in Thailand - Kongsamut, Piyabha (IMF Working Papers; Working Paper ;, 2003)
Recent crises in emerging markets have highlighted the role of the corporate sector in transmitting financial shocks to the macroeconomy. This paper takes stock of the performance of the Thai corporate sector in emerging from the Asian crisis, and discusses remaining challenges and vulnerabilities. Econometric evidence is presented on the impact of excess leverage on performance. Debt levels, though high, have fallen from post-crisis peaks, while returns and corporate cash flows have stabilized. However, the aggregate picture masks significant firm-level variation, which is analyzed by examining estimated distributions for various indicators across firms.